SUATU TINJAUAN TERHADAP PERANAN PEMERINTAH KOTA SAMARINDA PADA PRODUKTIVITAS INDUSTRI KECIL DAN MENENGAH YANG ADA DI KOTA SAMARINDA - ., Utomo . (PREDIKSI, 2014)
ABSTRAKT From koesinoer made to artisans weaving sheath samantha is in jl . These P Gg Weaving Ex . Samarinda Seberang Masjid Al - Rasid calculation ( 1994:80 ) , with ruus as follows : Ni = N i x n N Description : ni = Ukurean sempel each Crafters Ni = Population Each Crafters N = Population at 5 KUB n = Size Sempel By using the above formula , it will result in the distribution of samples in each Business Group as follows : X = 135 + 165 +195 3 = 495 = 165 3 indicates that the variable role of government composed of three indicators showed good because getting 165 Score This score is above the medium under kuwartil II be entered in the Role of Government gori said Good . Y = 193 + 190 +192 + 194 +160 + 193 +192 +194 +194 9 = 1702 = 189 9 Variable Productivity with 9 indicators show Good for getting these scores are above 189 medium under kuwartil II so Productivity artisans included in the category Good.with 12 indicators there are 2 indicator is still below the average of that provision and the Role of Productivity Indicator is still necessary as well as increased attention from Government